Formation of bone-like apatite on polymeric surfaces modified with -SO3H groups - Leonor, I. B. (2006)
Sulfonic groups (-SO3H) were covalently attached on different polymeric surfaces enabling them to induce apatite nucleation, for developing bioactive apatite-polymer composites with a bonelike 3-dimensional structure. High molecular weight polyethylene (HMWPE) and ethylene-co-vinyl alcohol co-polymer (EVOH) were used. The polymers were soaked in two types of sulphate-containing solutions with different concentrations, sulphuric acid (H2SO4) and chlorosulfonic acid (ClSO3H). To incorporate calcium ions into to the sulfonated polymers, the samples were soaked in a saturated Ca(OH)2 solution for 24 hours. After soaking of the samples in a simulated body fluid (SBF), formation of an apatite layer on both surfaces was observed. The results obtained prove the validity of the proposed concept and show that the -SO3H groups are effective on inducing apatite nucleation on the surface of these polymers.